2012
DOI: 10.1002/bit.24456
|View full text |Cite
|
Sign up to set email alerts
|

Modification of macroporous titanium tracheal implants with biodegradable structures: Tracking in vivo integration for determination of optimal in situ epithelialization conditions

Abstract: Previously, we showed that macroporous titanium implants, colonized in vivo together with an epithelial graft, are viable options for tracheal replacement in sheep. To decrease the number of operating steps, biomaterial-based replacements for epithelial graft and intramuscular implantation were developed in the present study. Hybrid microporous PLLA/titanium tracheal implants were designed to decrease initial stenosis and provide a surface for epithelialization. They have been implanted in New Zealand white ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…This macroporous titanium is characterized by multiple layers of hexagonal pores with a 640 lm diameter, 8 macroporosity that facilitates cell migration and bone deposition. 9 It has been shown that porous titanium implants can be enriched, either directly [10][11][12] or by association with biocompatible hydrogels, [13][14][15][16] with antibiotics, 14 VEGF, 15 and FGF-2. 16 To improve implant osseointegration, osteogenic factors can be used for implant enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…This macroporous titanium is characterized by multiple layers of hexagonal pores with a 640 lm diameter, 8 macroporosity that facilitates cell migration and bone deposition. 9 It has been shown that porous titanium implants can be enriched, either directly [10][11][12] or by association with biocompatible hydrogels, [13][14][15][16] with antibiotics, 14 VEGF, 15 and FGF-2. 16 To improve implant osseointegration, osteogenic factors can be used for implant enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…These unknown factors are supposed to be delivered by some specific surface features of the TiO2 layer, such as crystalline phase, exposed facet, electron structure and surface defect, which together could create a chemically active solid surface that may catalyze some heterogeneous redox reactions or facilitate the adsorption and desorption of macromolecules in the human body. It must be noted that the effect of such surface features have yet been investigated extensively in conjunction with TiO2 photocatalysts and semiconductors but they have been disregarded in relation to indwelling implants 3.2.Surface modification of Titanium to control cell response Cell attachment and spreading on titanium is a well-established phenomenon (Le Guéhennec et al, 2007, Sjöström et al, 2013, Koenig et al, 2016, Schultz et al, 2007, Vrana et al, 2012, Regis et al, 2015. Nevertheless, lack of osseointegration on untreated titanium implants is often associated with implant failure mainly due to the difficulty of the material to establish a strong bond with bone.…”
Section: 1immune Response To Titaniummentioning
confidence: 99%
“…However, continuation of this process can lead to restenosis and in the presence of the pore gradient due to the PLLA structure, no fibroblast presence was observed after 6 weeks of implantation 20 . During this period HPLC analysis showed distinct peaks that fluctuate during the time course of implantation.…”
Section: Analysis Of Blood Plasma With Hplc and Subsequent Sequencingmentioning
confidence: 99%
“…Mercury Porosimeter measurements showed distinct peaks that correspond to the pores on the both sides of the implant and the smaller interdispersed pores. However the more crucial data is the difference between the porosities of intraluminal and extraluminal surfaces, which can be analyzed by Image J for pore size distribution with a scanning electron microscope (SEM) 20 . For verification of the pore gradient, freeze-fracture the samples and observe the cross-section with SEM.…”
Section: Preparation Of Micropore Gradients In Macroporous Metallic Imentioning
confidence: 99%